μ3-Oxido-tris{dichlorido[1,3-bis(1,3,5-trimethylphenyl)imidazol-2-ylidene]gold(III)} bis(trifluoromethanesulfonyl)imide-[bis(trifluoromethanesulfonyl)imide]silver(I) (1/2) - Pažický, Marek; Rominger, Frank; Limbach, Michael (Acta crystallographica. Section E, Structure reports online, 2010)
The unusual trinuclear AuIII oxide title complex, [Au3Cl6O(C21H24N2)3](C2F6NO4S2)·2[Ag(C2F6NO4S2)], is the side product of the reaction of [1,3-bis(1,3,5-trimethylphenyl)imidazol-2-ylidene]dichloridophenylgold(III) with silver bis(trifluoromethanesulfonyl)imide in the presence of traces of water. In contrast to corresponding AuI complexes, the core structure of the title compound is planar. Two silver(I) bis(trifluoromethanesulfonyl)imide units are loosely bound to the complex cation. Here the silver atoms, disordered over two positions in a 0.870 (2):0.130 (2) ratio, interact either with the lone pairs of three chlorine ligands or two chlorine ligands and one edge of the mesityl π-system. The crystal under investigation was a partial racemic twin.